FILSAFAT ILMU-ILMU KEISLAMAN INTEGRALISTIK: STUDI PEMIKIRAN KUNTOWIJOYO - Muhammad Zainal Abidin (Jurnal Ilmiah Ilmu Ushuluddin, 2014)
This paper departs from the spirit to build the integrative science. Development of integrative science is an importantissue for the Islamic world, not just merely as part of an effort to overcome the problem of the dichotomy of science,which is the root of the problem of dropping people and their stuttering in facing the challenges of modernity, but alsobe an option in solving various problems of contemporary humanity, which can not be solved completely by usingWestern science.The findings of this paper. First, the construction of the Islamic paradigm in the development ofintegrative science rests on spirit of Islamic scientification. Secondly, the paradigm of Islam is considered to have strongprospects in developing the Islamic sciences that relevant to the realities and needs of Muslims.